2018
DOI: 10.1021/acs.jpcb.8b01819
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Pollutant Uptake Properties of Molecular Templated Polymers Containing β-Cyclodextrin

Abstract: Templated (T) and nontemplated (NT) cross-linked materials containing β-cyclodextrin (β-CD) and epichlorohydrin (EPH) were prepared at variable β-CD-EPH ratios (1:15, 1:20, and 1:25) in the presence and absence of a molecular template (toluene). The structural characterization of the materials was carried out using spectroscopy (Fourier transform infrared, solids C NMR, and scanning electron microscopy) and thermogravimetric analysis. The adsorption properties were studied with phenol-based adsorbates (2,4,6-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The Double constant equation is a dynamic empirical formula suitable for characterizing the complex reaction process. The Elovich equation is also an empirical formula to explain the adsorption process of adsorbents on irregular surfaces with a large number of active adsorption sites, and to illuminate non-ideal adsorption state [38,39,40,41]. The experimental data were fitted to the Pseudo-first-order kinetic model (Equation (9)), the Pseudo-second-order kinetic model (Equation (10)), the Double constant kinetic model (Equation (11)), and the Elovich kinetic model (Equation (12)).…”
Section: Resultsmentioning
confidence: 99%
“…The Double constant equation is a dynamic empirical formula suitable for characterizing the complex reaction process. The Elovich equation is also an empirical formula to explain the adsorption process of adsorbents on irregular surfaces with a large number of active adsorption sites, and to illuminate non-ideal adsorption state [38,39,40,41]. The experimental data were fitted to the Pseudo-first-order kinetic model (Equation (9)), the Pseudo-second-order kinetic model (Equation (10)), the Double constant kinetic model (Equation (11)), and the Elovich kinetic model (Equation (12)).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that nitrophenols with variable hydrophile-lipophile balance (HLB) can be adsorbed at inclusion versus interstitial domains of epichlorohydrin cross-linked materials that contain b-CD. 51 This can be understood since the interstitial domains that contain epichlorohydrin may possess greater hydrophile character over urethane linkages that contain lipophile cross-linker units such as TPE. As well, polysaccharide materials undergo solvent swelling in water, where judicious selection of adsorbate such as nitroarenes 42 with variable electron deciency can provide insight on the structural characterization and the uorescence quenching mechanism, as described below.…”
Section: Gas Adsorption Resultsmentioning
confidence: 99%
“…The kinetic uptake profile of FL against time with CS-Ac-An was obtained using a one-pot kinetic method [78]. The results of the kinetic study at 23 • C are shown in Figure 7, where the adsorption capacity (Q t ) increased in the first 60 min and remained constant thereafter.…”
Section: Kinetic Studies Of Fl Using Cs-ac-anmentioning
confidence: 99%